2018
DOI: 10.1080/13625187.2018.1449825
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding patterns for the Liletta® levonorgestrel 52 mg intrauterine system

Abstract: Purpose: Evaluate bleeding patterns for the Liletta V R levonorgestrel 52 mg intrauterine system (IUS) using the World Health Organization Belsey definitions. Material and methods: This prospective multicenter trial evaluates the efficacy and safety of Liletta V R (Clinicaltrials.gov NCT00995150). We evaluated bleeding patterns for 1700 nulliparous and multiparous women using a daily diary completed by participants for the first 2 years and by questionnaire every 3 months thereafter. We assessed amenorrhea rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
2
11
0
Order By: Relevance
“…This retrospective analysis of early bleeding pattern data builds on the knowledge provided by previously published data from the phase II and III trials of the 19.5 mg LNG-IUS [4,5,7] and shows that women generally experience progressively lighter (i.e., more spotting and less bleeding) and shorter bleeding episodes with use of the 19.5 mg LNG-IUS in months 1 and 3. Reported discontinuation rates due to bleeding (4.5% at 3 years and 5.2% at 5 years) reflect those observed in other studies [5,21].…”
Section: Discussionsupporting
confidence: 83%
“…This retrospective analysis of early bleeding pattern data builds on the knowledge provided by previously published data from the phase II and III trials of the 19.5 mg LNG-IUS [4,5,7] and shows that women generally experience progressively lighter (i.e., more spotting and less bleeding) and shorter bleeding episodes with use of the 19.5 mg LNG-IUS in months 1 and 3. Reported discontinuation rates due to bleeding (4.5% at 3 years and 5.2% at 5 years) reflect those observed in other studies [5,21].…”
Section: Discussionsupporting
confidence: 83%
“…Women in these studies also had different rates of nulliparity and mean BMI; the levonorgestrel 52 mg IUS study included more nulliparous and obese women [12]. Although variations in characteristics of the study populations could account for some bleeding pattern differences, analyses of the levonorgestrel 52 mg IUS data shows no difference in bleeding patterns based on parity or BMI [8]. Thus, the likelihood that these differences are impacting the outcomes is low.…”
Section: Discussionmentioning
confidence: 99%
“…The levonorgestrel 19.5 mg and 13.5 mg products had available diary data through 3 years [12]. We limited the comparisons of prolonged, frequent, infrequent and irregular bleeding to two years because the levonorgestrel 52 mg IUS studies only used daily diaries for the first two years after which investigators obtained bleeding information by interview [8]. The LNG 52 mg IUS data uses the interview information to provide amenorrhea rates at 3 years which allowed an amenorrhea comparison after two years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, bleeding pattern seems to be a crucial aspect of contraception for women, since Marions et al reported that the level of satisfaction was dependent on the frequency and volume of bleeding and dysmenorrhea [39]. Several authors obtained similar amenorrhea rates in nulliparous LNG-IUS users-from 18% to 26% at the end of the first year of use, and even up to 36% at the end of the third year in the study by Schreiber et al [33,[35][36][37]39,40,44,45]. Moreover, the latter found that: infrequent bleeding rate increased from 12% to 30%, frequent bleeding rate decreased from 29% to 4%, prolonged bleeding rate decreased from 50% to 2% and irregular bleeding rate decreased from 39% to 4% during the last 90 days of the second year, in comparison to the first 90 days of usage.…”
Section: Bleeding Patternmentioning
confidence: 95%